Anthocyanins in Malatinta fruit extract as indicator in acid-base titrations. - Matullano, Scarlet Gem M.
Some natural extracts from plants are sensitive to pH and have shown potential to replace standard acid/base indicators which are synthetic, toxic, costly and non readily available. Because of this, the search for natural compounds as an acid/base indicator was started and has gained increasing attention recently. This study was conducted to evaluate the use of anthocyanins in malatinta (Phyllanthus reticulatus Poir) fruit extract (MFE) as an acid/base indicator in different types of acid/base titrations. The efects of light, temperature, and presence of oxidants and reductants on the stability of anthocyanins and on the performance (accuracy and sensitivity) of the MFE as an acid/base indicator were determined. Results showed that the total monomeric anthocyanin content in MFE was high, indicating that malatinta fruits can be significant source of anthocyanins. Acid/base titration experiments showed that there was no significant differences between the results obtained by MFE and those of standard indicators. This in turn suggests that MFE can be alternative standard indicators in routine acid/base titrations. Light, elevated temperature and presence of oxidants and reductant affected significantly the stability of anthocyanins; however, these factors did not significantly affect the performance of MFE as an acid/base indicator. Determination of pKa and transition ranges, comprehensive degradation studies, and further characterization and quantification of anthocyanins and other natural components in MFE are recommended to better understand their behavior and stability as an acid/base indicator.